Chinese and Western Investments in Africa - (:unkn) unknown (My University, 2019)
Chinese investments in African countries have increased massively in the last two decades. Critics have been vociferous for or against the Afro-Chinese relationship depending on their convictions making it a bit difficult to have an objective analysis on the issue.African nations and their leaders have repeatedly shown preference for Western culture and civilization due to or despite their respective and common historical experiences.When given the option, African states have always embraced Western companies and businesses. This can be seen in the larger majority of Western businesses established in the continent compared to those from other parts of the world.Foreign direct investments into Africa have also been traditionally from the West. But this preference for the West at least since the age of independence has not yielded the anticipated results. And this is the main reason why the Chinese are seen as an alternative today. Using the most recent research and data on this topic, this paper endeavors to analyze the nascent Chinese policies and investments in Africa comparing and contrasting their successes and failures compared to those of Western countries.
Keywords: African Research